The use of fenestrated and branched endovascular aneurysm repair for juxtarenal and thoracoabdominal aneurysms: a systematic review and cost-effectiveness analysis - Nigel Armstrong; Laura Burgers; Sohan Deshpande; Maiwenn Al; Rob Riemsma; SR Vallabhaneni; Peter Holt; Johan Severens; Jos Kleijnen (Health Technology Assessment, 2014)
Background: Patients with large abdominal aortic aneurysms (AAAs) are usually offered reparative treatment given the high mortality risk. There is uncertainty about how to treat juxtarenal AAAs (JRAAAs) or thoracoabdominal aortic aneurysms (TAAAs). Endovascular repair of an abdominal aortic aneurysm (EVAR) is often seen as safer and easier than open surgical repair (OSR). However, endovascular treatment of JRAAAs or TAAAs requires specially manufactured stent grafts, with openings to allow blood to reach branches of the aorta. Commissioners are receiving increasing requests for fenestrated EVAR (fEVAR) and branched EVAR (bEVAR), but it is unclear whether or not the extra cost of fEVAR or bEVAR is justified by advantages for patients. Objective(s): To assess the clinical effectiveness, safety and cost-effectiveness of fEVAR and bEVAR in comparison with conventional treatment (i.e. no surgery) or OSR for two populations: JRAAAs and TAAAs. Data sources: Resources were searched from inception to October 2013, including MEDLINE (OvidSP), EMBASE (OvidSP) and the Cochrane Central Register of Controlled Trials (Wiley) and, additionally, for cost-effectiveness, NHS Economic Evaluation Database (NHS EED; Wiley) and EconLit (EBSCOhost). Conference abstracts were also searched. Review methods: Studies were included based on an intervention of either fEVAR or bEVAR and a comparator of either OSR or no surgery. For clinical effectiveness, observational studies were excluded only if they were not comparative, i.e. explicitly selected on the basis of prognosis. Results: For clinical effectiveness, searches retrieved 5253 records before deduplication. Owing to overlap between the databases, 1985 duplicate records were removed. Of the remaining 3268 records, based on titles and abstracts, 3244 records were excluded, leaving 24 publications to be ordered. All 24 studies were excluded as none of them satisfied the inclusion criteria. Sixteen studies were excluded on study design, six on intervention and two on comparator. Five out of 16 studies excluded on study design reported a comparison. However, all of the studies acknowledged that they had groups that were not comparable at baseline given that they had selectively assigned younger, fitter patients to OSR. Therefore, these studies were considered ‘non-comparative’. For cost-effectiveness, searches identified 104 references before deduplication. Owing to overlap between the databases, 34 duplicate records were removed. Of the remaining 70 records, seven were included for the full assessment based on initial screening. After a full-text review, no studies were included. Because of the lack of clinical effectiveness evidence and difficulty in estimating costs given the rapidly changing and variable technology, a cost-effectiveness analysis (CEA) was not performed. Instead a detailed description of modelling methods was provided. Conclusions: Despite a thorough search, no studies could be found that met the inclusion criteria. All studies that compared either fEVAR or bEVAR with either OSR or no surgery explicitly selected patients based on prognosis, i.e. essentially the populations for each comparator were not the same. Despite not being able to conduct a CEA, we have provided detailed methods for the conduct if data becomes available. Future work: We recommend at least one clinical trial to provide an unbiased estimate of effect for fEVAR/bEVAR compared with OSR or no surgery. This trial should also collect data for a CEA. Study registration: This study is registered as PROSPERO CRD42013006051. Funding: The National Institute for Health Research Health Technology Assessment programme.